HEAVY METAL POLLUTION AND THE ENVIRONMENT IN TIRUCHENDUR TALUK AND SRIVAIKUNDAM TALUK - Eucharista, Esther Isabella (International Journal of Research -GRANTHAALAYAH, 2017)
Heavy metals are naturally occurring elements that have a high atomic weight than that of water. Their multiple industrial, domestic, agricultural, medical and technological applications have led to their wide distribution in the environment; raising concerns over their potential effects on human health and the environment. The maximum Zn concentration was noticed in the year 2012 as 24.47±0.57µg/l in the water bodies of Tiruchendur and Srivaikundam taluk at station X. The highest Zn concentration was obtained in the water sediments as 272.33±5.01 µg/g at station 1 in the year 2012 and the concentration was high in the phytoplankton as 34.314±4.239 µg/g at station V in the year 2011. During the year 2012, the cu was found high as 22.53±15.70 µg/l at station III in the water bodies. In the sediments it was high as 63.03±13.85 µg/l at station XI during 2011. In the phytoplankton the maximum concentration was noticed at station VIII as 13.564±2.797 µg/g during 2011. During the year 2011 the highest concentration of Pb was emphasized at station VI as 11.31±1.63 µg/l in the water bodies. In the water sediments it was high at station V as 64.11±11.96 µg/g during 2011. In the phytoplankton, the concentration was measured highest at station II as 4.343±0.976 µg/g dry weight in the year 2012. All the heavy metals such as Zn, Cu and Pb were exceeded the Shale reference background value. This review provides an analysis of their environmental occurrence and potential for human exposure.